Preparation and Characterization of p-Anisaldehyde Microcapsules and Its Application in Carrot Preservation - WANG Ting, LONG Haitao, LI Yongcai, LI Li, WANG Xiwang, BI Yang (Shipin Kexue)
In order to develop plant essential oil microcapsules and evaluate their application in the preservation of fruits and vegetables, microcapsules were prepared by spray-drying method using p-anisaldehyde as the core material and octenyl succinic anhydride-modified starch and chitosan as the wall material, and the effect of the microcapsules on the preservation of carrots was investigated. The results showed that p-anisaldehyde was successfully encapsulated. The emulsion added with 3.5 g of p-anisaldehyde had good dispersity with an encapsulation rate of 77.21%. The formed microcapsules were spherical with a smooth surface, and the thermal stability of anisaldehyde was improved after encapsulation. Further studies showed that fumigation with anisaldehyde microcapsules effectively inhibited the respiration intensity of carrots during storage, delayed the increase in L* and the decrease in a* and b*, slowed down the decrease in soluble solids content and the increase in mass loss, and maintained textural properties such as hardness. The fumigation treatment also increased the activities of peroxidase (POD), superoxide dismutase (SOD) and catalase (CAT) in carrot tissues. In conclusion, the anisaldehyde microcapsules could effectively maintain the quality of carrots during postharvest storage.